Copper alloy powder, laminated object, manufacturing method for laminated object, and various metal parts

JP7630554B2Active Publication Date: 2025-02-17FURUKAWA ELECTRIC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023087862
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-06-14
Filing Date
2023-05-29
Publication Date
2025-02-17
Estimated Expiration
2039-03-11

AI Technical Summary

Benefits of technology

【0014】 本発明は、質量%で、Cr:0.010~1.50%、Zr:0.010~1.40%を含有し、残部が銅および不可避不純物からなることにより、高強度、高導電率および優れた耐熱性の全てを具備した積層造形物の製造を可能にする銅合金粉末、積層造形物および積層造形物の製造方法、ならびに例えばモーターのブラシ、ブレーキパッド、抵抗溶接用電極、放電加工用電極、スリップリング、軸受のような各種金属部品の提供が可能になった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630554000002
    Figure 0007630554000002
  • Figure 0007630554000001
    Figure 0007630554000001
Patent Text Reader

Abstract

To provide: a copper alloy powder that enables production of a layered / molded product having high strength, high electrical conductivity and excellent heat resistance; a layered / molded product, and a method for producing the same; and various metal parts such as a motor brush, a brake pad, an electrode for resistance welding, an electrode for electric discharge machining, a slip ring, and a bearing.SOLUTION: A copper alloy powder of this invention contains, by mass, 0.010-1.50% of Cr and 0.05-1.40% of Zr, with the remainder comprising copper and unavoidable impurities. A layered / molded product of this invention is formed by melting and solidifying a copper alloy powder that contains, by mass, 0.010-1.50% of Cr and 0.05-1.40% of Zr, with the remainder comprising copper and unavoidable impurities. The layered / molded product has: an apparent density of 94% or more and 100% or less; and an electrical conductivity of 50% IACS or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to copper alloy powder, an additively manufactured product, a method for manufacturing an additively manufactured product, and various metal parts. In particular, by using copper alloy powder containing chromium and zirconium as the raw material powder and utilizing the rapid solidification phenomenon caused by additive manufacturing, the present invention realizes the production of a chromium-zirconium copper alloy as an additively manufactured product that has high strength, high electrical conductivity, and excellent heat resistance. [Background technology]

[0002] Metallic materials that are required to have high strength, high electrical conductivity, and excellent heat resistance, such as materials for electrodes used in resistance welding and electric discharge machining, include copper alloys containing chromium and zirconium. Zirconium contained in such copper alloys can exhibit the most excellent heat resistance effect in a solid solution state, but in actual manufacturing processes, the temperature range in which zirconium precipitates is often maintained, so that zirconium does not form a solid solution in the copper base material but becomes a precipitate, and the precipitate becomes coarse, which tends to reduce heat resistance. Chromium-containing copper alloys (Cu-Cr alloys) and chromium-zirconium-containing copper alloys (Cu-Cr-Zr alloys) are age-hardened copper alloys with relatively high strength and electrical conductivity, and are generally applied to small parts such as resistance welding electrode materials and spring materials, and large parts such as water-cooled molds. (For example, see Non-Patent Document 1)

[0003] Also, it is known that a chromium-zirconium copper alloy (Cu-Cr-Zr alloy), which is a chromium-containing copper alloy (Cu-Cr alloy) with zirconium added, has improved intermediate temperature brittleness that is generally observed in copper alloys, has a higher annealing softening temperature than chromium copper, and has higher strength (see, for example, Non-Patent Document 1).

[0004] In chromium-containing copper alloys (Cu-Cr alloys), the unprocessed material shows a large age hardening, while the processed material tends to soften due to recovery during aging at around 300°C, reaches a maximum hardness at about 400°C, and tends to soften rapidly at higher temperatures (see, for example, Non-Patent Document 2).

[0005] Conventional Cu-Cr alloys and Cu-Cr-Zr alloys are generally produced by metal mold casting, and therefore the cooling rate during casting cannot be increased. As a result, the crystal grains that make up the solidification structure become coarse, and zirconium cannot exist in a solid solution state in the copper base material and instead exists locally in the form of precipitates, which can lead to non-uniform product quality and the inability to obtain stable mechanical properties.

[0006] Conventionally, metal products have been manufactured from metals and alloys by processing methods such as casting, extrusion, cutting, and powder metallurgy.

[0007] As a processing technology for metal products, additive manufacturing using metal powder has been attracting attention. The advantage of this method is that it makes it possible to create complex shapes that are not possible with cutting processes. To date, there have been reported examples of additive manufacturing using iron-based alloy powder, aluminum alloy powder, titanium alloy powder, and the like. However, at present, the types of metals that can be used are limited, and there are certain restrictions on the metal products that can be used. (See, for example, Patent Document 1.)

[0008] By using additive manufacturing, it is possible to create products with complex shapes that cannot be manufactured by conventional methods, and by performing design on software, it is also possible to create products that require tailor-made products.In addition, by irradiating a laser or electron beam at a specific position on a powder layer composed of powder, it is possible to melt metals and alloys, and then rapidly cool and solidify them at a high cooling rate that cannot be achieved with normal bulk, making it possible to develop materials and products with new properties.

[0009] However, copper has a low light absorption rate for lasers, making it difficult to set the molding conditions compared to iron-based alloy powders, aluminum alloy powders, etc., and since the density of the additively manufactured object after molding is low, conventional additively manufactured objects made using current copper alloy powders have not yet been able to produce copper alloys that possess all of high strength, high electrical conductivity, and excellent heat resistance. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2017-115220 A [Non-patent literature]

[0011] [Non-Patent Document 1] Shinji Tanaka et al., "Solidification Structure of Cu-Cr and Cu-Cr-Zr Alloys," Journal of the Japan Institute of Metals, Vol. 74, No. 6, pp. 356-364 [Non-Patent Document 2] Suzuki, Hisashi et al., "Strength and aging structure of Cu-Cr-Zr alloys", Journal of the Japan Institute of Metals, Vol. 33, No. 5, pp. 628-633 Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide a copper alloy powder that enables the production of an additively molded product that has high strength, high electrical conductivity, and excellent heat resistance by optimizing the composition of the material powder, an additively molded product, a method for producing an additively molded product, and various metal parts such as motor brushes, brake pads, resistance welding electrodes, electric discharge machining electrodes, slip rings, and bearings. [Means for solving the problem]

[0013] The gist and configuration of the present invention are as follows. (1) A copper alloy powder for additive manufacturing, comprising, by mass%, 0.010 to 1.50% Cr, 0.010 to 1.40% Zr, and the remainder being copper and unavoidable impurities. (2) The copper alloy powder according to (1) above, having an average particle size in the range of 10 μm or more and 40 μm or less. (3) The copper alloy powder according to (1) or (2) above, in which the 50% particle size (d50) of the cumulative particle size distribution obtained by measurement on a volume basis is 10 to 40 μm and the 10% particle size (d10) of the cumulative particle size distribution is 1 to 30 μm. (4) The copper alloy powder according to the above (3), having a 90% particle size (d90) of an integrated particle size distribution measured on a volume basis of 30 to 70 μm. (5) The copper alloy powder according to any one of the above (1) to (4), further containing one or more selected from the group consisting of Pb: 0.01 to 1.0%, Bi: 0.01 to 1.0%, Ca: 0.01 to 1.0%, Sr: 0.01 to 1.0%, Ba: 0.01 to 1.0%, Te: 0.01 to 1.0%, Si: 0.01 to 1.0%, Sn: 0.01 to 1.0%, Mg: 0.01 to 1.0%, Ni: 0.01 to 1.0%, Ag: 0.01 to 1.0%, and Mn: 0.01 to 1.0%. (6) An additive manufacturing product formed by melting and solidifying a copper alloy powder containing, by mass%, 0.010 to 1.50% Cr, 0.010 to 1.40% Zr, and the remainder being copper and unavoidable impurities, the additive manufacturing product having an apparent density of 94% or more and 100% or less and an electrical conductivity of 50% IACS or more. (7) The layered object according to (6) above, wherein the size of precipitates present in the layered object is 5 μm or less. (8) The layered object according to claim 6 or 7, further comprising one or more selected from the group consisting of Pb: 0.01-1.0%, Bi: 0.01-1.0%, Ca: 0.01-1.0%, Sr: 0.01-1.0%, Ba: 0.01-1.0%, Te: 0.01-1.0%, Si: 0.01-1.0%, Sn: 0.01-1.0%, Mg: 0.01-1.0%, Ni: 0.01-1.0%, Ag: 0.01-1.0%, and Mn: 0.01-1.0%. (9) A method for manufacturing an additively molded object, comprising: a first step of forming a powder layer using the copper alloy powder described in any one of (1) to (5) above; and a second step of melting and solidifying the copper alloy powder present at a predetermined position in the powder layer to form a molded layer, characterized in that the first step and the second step are repeated sequentially to stack the molded layers. (10) The method for producing an additively molded object described in (9) above, further comprising at least one of a heat treatment process and a forging process after the repeated stacking of the molded layers is completed. (11) A motor brush formed using the copper alloy powder according to any one of (1) to (5) above or the layered object according to any one of (6) to (8) above. (12) A brake pad formed using the copper alloy powder according to any one of (1) to (5) above or the layered object according to any one of (6) to (8) above. (13) A resistance welding electrode formed using the copper alloy powder according to any one of (1) to (5) above or the layered object according to any one of (6) to (8) above. (14) An electrode for electrical discharge machining formed using the copper alloy powder according to any one of (1) to (5) above or the layered object according to any one of (6) to (8) above. (15) A slip ring formed using the copper alloy powder according to any one of (1) to (5) above or the layered product according to any one of (6) to (8) above. (16) A bearing formed using the copper alloy powder according to any one of (1) to (5) above or the layered product according to any one of (6) to (8) above. Effect of the Invention

[0014] The present invention contains, by mass, 0.010 to 1.50% Cr, 0.010 to 1.40% Zr, with the remainder being copper and unavoidable impurities, making it possible to provide a copper alloy powder that enables the production of an additively molded product that has all of high strength, high electrical conductivity, and excellent heat resistance, as well as an additively molded product and a method for producing an additively molded product, and various metal parts such as motor brushes, brake pads, resistance welding electrodes, electric discharge machining electrodes, slip rings, and bearings.

[0015] In particular, by incorporating chromium and zirconium into copper, it is possible to improve the light absorption rate, and therefore to design a powder with excellent formability.

[0016] In addition, by using such alloy powder, the density of the additive manufacturing product can be improved, and the high density of the additive manufacturing product can improve the strength and electrical conductivity compared to pure copper.

[0017] Furthermore, by using the additive manufacturing method, after melting the raw copper alloy powder, the molten metal can be rapidly solidified at a cooling rate that is significantly faster than that of the conventional casting method for producing copper alloys. As a result, the crystal grains can be refined by this rapid solidification, thereby improving the strength, and the formation of precipitates of chromium and zirconium contained in the copper alloy is effectively suppressed, thereby improving the heat resistance. [Brief description of the drawings]

[0018] [Figure 1] 1(a) and (b) show two types of electrodes as examples of parts manufactured by an additive manufacturing device (3D printer) using the copper alloy powder according to the present invention as a material, where FIG. 1(a) is a schematic diagram of an electrode for resistance welding, and FIG. 1(b) is a schematic diagram of an electrode for electric discharge machining. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Next, preferred embodiments of the copper alloy powder according to the present invention will be described in detail below. (copper alloy powder) The copper alloy powder of the present embodiment contains, by mass%, Cr: 0.010 to 1.50%, Zr: 0.010 to 1.40%, and the remainder being copper and unavoidable impurities.

[0020] First, the reasons for limiting the component composition of the copper alloy powder of the present invention will be explained. [Component composition] <Essential ingredients> ·Cr:0.010~1.50% by mass Cr (chromium) is a component that has the effect of improving strength and heat resistance, and is also an important element that can exert the effect of significantly increasing the light absorption rate of laser light having a wavelength of 1.2 μm or less, especially fiber lasers having a wavelength of 1.065 μm, even with a small amount. In order to exert such an effect, the Cr content is preferably 0.010 mass% or more. Also, when the Cr content exceeds 1.50 mass%, the Cr 2 Zr or Cu 3 This is because the precipitates of Zr and the like become coarse, and the effect of improving strength and heat resistance cannot be expected.For this reason, the Cr content is preferably set in the range of 0.010 to 1.50 mass%.

[0021] ·Zr:0.010~1.40% by mass Zr (zirconium) is a component that has the effect of improving heat resistance, and is also an important element that can exert the effect of significantly increasing the light absorption rate of laser light having a wavelength of 1.2 μm or less, especially fiber lasers having a wavelength of 1.065 μm, even with a small amount. In order to exert such an effect, the Zr content is preferably 0.010 mass% or more. Furthermore, if the Zr content exceeds 1.40 mass%, Cr 2 Zr or Cu 3 This is because the precipitates of Zr or the like become coarse, and the effect of improving strength and heat resistance cannot be expected. Therefore, the Zr content is preferably set in the range of 0.010 to 1.40 mass %.

[0022] <Optional addition ingredients> In the present invention, the above-mentioned Cr and Zr are essential components, but other than these components, for example, one or more elements selected from the group consisting of Pb: 0.01 to 1.0%, Bi: 0.01 to 1.0%, Ca: 0.01 to 1.0%, Sr: 0.01 to 1.0%, Ba: 0.01 to 1.0%, Te: 0.01 to 1.0%, Si: 0.01 to 1.0%, Sn: 0.01 to 1.0%, Mg: 0.01 to 1.0%, Ni: 0.01 to 1.0%, Ag: 0.01 to 1.0%, and Mn: 0.01 to 1.0% in mass % may be appropriately contained as optional components according to the required performance, etc. These optional added components are elements added to improve the light absorption characteristics, and in order to improve such characteristics, it is preferable to contain 0.010% or more of each added component. On the other hand, even if the content of each additive component is more than the upper limit of the above content range, no further improvement effect can be expected. Also, 0.05% or more and 0.3% or less is more preferable. Furthermore, when two or more kinds of these optional additive components are used, the total content is preferably 0.02 to 2.0 mass %, from the viewpoint of expecting an improvement effect of light absorptance.

[0023] <Remainder> Other than the above-mentioned essential components and optional components, the remainder is composed of Cu and inevitable impurities. Note that the "unavoidable impurities" referred to here are impurities that are present in the raw materials of copper alloy particles or that are inevitably mixed in during the manufacturing process, and are essentially unnecessary, but are allowed in trace amounts, approximately 0.05 mass% or less, because they do not affect the properties of the copper alloy particles.

[0024] [Average particle size and particle size distribution of powder] The copper alloy powder of this embodiment preferably has an average particle size in the range of 10 μm or more and 40 μm or less.

[0025] In addition, the copper alloy powder of this embodiment preferably has a cumulative particle size distribution measured on a volume basis, with a 50% particle size (d50) of 10 to 40 μm and a 10% particle size (d10) of 1 to 30 μm, and more preferably a 90% particle size (d90) of 30 to 70 μm.

[0026] The term "average particle diameter" as used herein means the volume average diameter MV. The term "50% particle diameter d50" is also called the median diameter, and means the particle diameter at which the copper alloy powder is accumulated from the small side to 50% volume in the cumulative particle size distribution obtained by measuring on a volume basis. Furthermore, the term "10% particle diameter d10" means the particle diameter at which the particles are accumulated from the small side to 10% volume in the cumulative particle size distribution obtained by measuring on a volume basis. In addition, the term "90% particle diameter d90" described later means the particle diameter at which the particles are accumulated from the small side to 90% volume in the cumulative particle size distribution obtained by measuring on a volume basis.

[0027] In the present invention, by setting the average particle size of the copper alloy powder in the range of 10 μm to 40 μm, the powder is easily melted during laser irradiation, and the density of the molded object can be improved. Also, by setting the 50% particle size d50 to 10 to 40 μm, the squeegeeability of the powder can be improved. Furthermore, by setting the 10% particle size d10 to 1 to 30 μm, the bulk density of the powder layer can be improved. As a result, during layered manufacturing, the copper-based powder can be spread so that the void ratio is small and the powder layer is densely packed to form a powder layer, and then, by irradiating the laser light, a layered product made of a high-density copper alloy can be manufactured. On the other hand, if the average particle size of the copper alloy powder is less than 10 μm, there is a problem that the powder scatters during laser irradiation, and if it exceeds 40 μm, there is a problem that the powder melts incompletely, resulting in a decrease in the density of the molded object and a decrease in the squeegeeability. Furthermore, if the 50% particle size d50 is less than 10 μm, the squeegeeability will be reduced, and if it is more than 40 μm, the bulk density of the powder will be reduced. Furthermore, if the 10% particle size d10 is less than 1 μm, the powder will scatter during laser irradiation, and if it is more than 30 μm, the bulk density of the powder layer will be reduced.

[0028] In addition, it is preferable that the 90% particle size (d90) of the cumulative particle size distribution measured on a volume basis is 30 to 70 μm in order to improve the bulk density of the powder layer. If the 90% particle size d90 is less than 30 μm, the bulk density of the powder layer may decrease due to the powder scattering during laser irradiation, while if the 90% particle size d90 is more than 70 μm, the bulk density of the powder layer may decrease, resulting in a decrease in the density of the molded object.

[0029] (Layered objects) The layered object of this embodiment is a layered object formed by melting and solidifying a copper alloy powder containing, by mass%, 0.010 to 1.50% Cr, 0.010 to 1.40% Zr, and the remainder being copper and unavoidable impurities, and the layered object has an apparent density of 94% to 100% and an electrical conductivity of 50% IACS or more. The reason why the apparent density is limited to 94% to 100% in the layered object of this embodiment is that a layered object made of a copper alloy formed using a conventional copper-based powder has a porosity greater than 6%, and the layered object's apparent density could not be 94% to 100%. However, in this embodiment, by optimizing the particle size and particle size distribution of the material powder as described above, a layered object made of a copper alloy with a high apparent density of 94% to 100% can be formed. In addition, an apparent density of 100% means the same as the theoretical density of a bulk copper alloy, and the layered object of this embodiment can be made of a high-density alloy that is equivalent to a copper alloy (bulk).

[0030] In addition, in this embodiment, by using Cu-Cr-Zr alloy powder, which has better formability than pure copper, for additive manufacturing, the internal porosity can be reduced and a high electrical conductivity of 50% IACS or more can be achieved.

[0031] Furthermore, the Cr present in the additive manufacturing product 2 Zr, Cu 3In order to obtain high strength and excellent heat resistance, it is preferable that the size of the precipitates of Zr, etc. is 5 μm or less. This is because the Cu-Cr-Zr alloy is an age-hardening copper alloy, and if the size of the precipitates becomes coarser than 5 μm, the strength and heat resistance tend to decrease.

[0032] (Method of manufacturing laminated objects) The method for manufacturing an additively molded product of this embodiment includes, for example, the above-mentioned first step of forming a powder layer with copper alloy powder and the second step of melting and solidifying the copper alloy powder present at a predetermined position of the formed powder layer to form a modeling layer, and the additively molded product can be manufactured by sequentially repeating the first and second steps to stack the modeling layers. More specifically, on a liftable modeling / processing table, copper alloy powder is spread to a thickness of about 0.05 mm by squeegeeing with a recoater to form a thin powder layer (first step), then laser light is irradiated based on CAD data to melt and solidify only the irradiated portion of the powder layer to form a modeling layer (second step), and the formation of a new powder layer and the irradiation of laser light are repeatedly performed using a laser additive manufacturing device (so-called 3D printer) to manufacture the additively molded product.

[0033] In addition, in order to obtain the required characteristics according to the application, it is preferable to further carry out at least one of a heat treatment process and a forging process after the repeated lamination of the shaping layers, as necessary.

[0034] Furthermore, when squeegeeing the copper alloy powder uniformly, applying a high frequency of 5 kHz or more to the recoater is more preferable because it reduces the porosity (void ratio) of the laminated object and increases the apparent density. This is because the phenomenon in which the copper alloy powder adheres to extremely fine surface scratches (size: up to 10 μm) on the surface of the blade used for squeegeeing and cannot be squeegeeed uniformly is improved by applying vibration. This causes the copper alloy powder to be dispersed more uniformly, which makes the gaps between the copper alloy powder particles with relatively large particle sizes uniform, and makes it easier for the copper alloy powder particles with relatively small particle sizes to enter these gaps. This makes the thermal resistance between the copper alloy powder particles uniform, which causes the light energy from the laser to be converted into thermal energy and diffuses uniformly, improving the apparent density of the copper alloy (laminated object) after melting and solidifying.

[0035] (Uses of the Layered Object of the Present Invention) The additive manufacturing product of the present invention can be applied to a wide range of technical fields and applications as various metal parts using copper alloy materials. Specifically, it can be applied to various metal parts, and is particularly suitable for use in motor brushes, brake pads, resistance welding electrodes, electric discharge machining electrodes, slip rings, bearings, etc. Figures 1(a) and (b) are examples of two types of electrodes from parts manufactured by an additive manufacturing device (3D printer) using the copper alloy powder according to the present invention as a material, where Figure 1(a) is a schematic diagram of a resistance welding electrode and Figure 1(b) is a schematic diagram of an electric discharge machining electrode.

[0036] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and includes all aspects encompassed by the concept of the present invention and the scope of the claims, and can be modified in various ways within the scope of the present invention. EXAMPLES

[0037] Next, in order to further clarify the effects of the present invention, examples and comparative examples will be described, but the present invention is not limited to these examples.

[0038] (Example 1 to 11, Reference examples 1~11 and Comparative Examples 1 to 5) Each component was weighed to obtain the composition shown in Table 1, and the weighed components were charged into a melting furnace and melted to produce copper alloys (ingots). Each of the produced copper alloys (ingots) was mechanically crushed, and the crushed copper alloys were melted and then sprayed in a gas atomizer to obtain copper alloy particles. In order to obtain fine particles, the inside of the spray tank of the gas atomizer was filled with 85% by volume N 2 and 15% by volume H 2 The atmosphere was filled with a mixture of CO and He gas or He gas. The collected copper alloy powder (particles) was sieved to classify the size. The particle size distribution of the classified material was measured using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation), and the 50% particle size (d50), 10% particle size (d10), and 90% particle size (d90) of the cumulative particle size distribution obtained by measuring on a volume basis were determined. The average particle size of the powder was determined using a light diffraction / scattering method.

[0039] Next, the prepared material powder was used to create a 130mm x 20mm x 9mm laminated object (copper alloy part) using a laser additive manufacturing device, Concept Laser M2 (wavelength 1065nm, output 400W), and a 120mm x 14mm x 3mm test piece was created by cutting to remove the surface powder and ensure a smooth surface. The apparent density (%) of each of the created objects (copper alloy parts) was measured using the Archimedes method. The apparent density (%) is calculated based on the true density (theoretical density of the bulk) of 100%.

[0040] The average particle size, d10, d50, and d90 of each material powder used as the material for the additive manufacturing object, as well as the porosity (%) and overall evaluation of each molded object (copper alloy part) are shown in Table 1. The overall evaluation was made based on the results of the apparent density, tensile strength, electrical conductivity, and heat resistance of the additive manufacturing object (copper alloy part) and was made on a five-level scale of "A", "B", "C", "D", and "E" according to the following criteria. In this example, the overall evaluations of "A", "B", "C", and "D" were deemed to be acceptable.

[0041] The apparent density of the additively manufactured object (copper alloy part) was rated as "○" when it was 95% or more, "△" when it was 94% or more and less than 95%, and "×" when it was less than 94%.

[0042] (Tensile strength) The tensile strength was measured (MPa) by performing a tensile test using a precision universal testing machine (manufactured by Shimadzu Corporation) in accordance with JIS Z2241:2001. The test was performed under the conditions of a gauge length of 5 cm and a deformation speed of 10 mm / min. Three pieces were measured for each tensile test, and the average value (N=3) was calculated. In this example, the tensile strength was rated as "○" when it was 250 MPa or more, "△" when it was 200 MPa or more but less than 250 MPa, and "×" when it was less than 200 MPa, as shown in Table 1.

[0043] (Heat resistance) Heat resistance was evaluated by preparing test pieces similar to those used to measure tensile strength, heating them in a heat treatment furnace at 300°C for 10 hours, conducting tensile tests under the same conditions as described above, measuring the tensile strength (MPa), and averaging the measured tensile strengths. The results are shown in Table 1, with the tensile strength after heating being 150 MPa or more lower than the tensile strength before heating marked as "x", the tensile strength after heating being 100 MPa or more but less than 150 MPa marked as "△", and the tensile strength after heating being less than 100 MPa marked as "○".

[0044] (conductivity) The electrical conductivity was measured for two of each test piece in a thermostatic chamber controlled at 20°C (±1°C) using a four-terminal method according to JIS H0505-1975, and the average value (%IACS) was calculated. The distance between the terminals was 100 mm. In this example, when the electrical conductivity was 60% IACS or more, it was evaluated as "○" for excellent electrical conductivity, when the electrical conductivity was 50% IACS or more and less than 60% IACS, it was evaluated as "△" for good electrical conductivity, and when the electrical conductivity was less than 50% IACS, it was evaluated as "×" for poor electrical conductivity, and the results are shown in Table 1.

[0045] <Overall Judgment> A: When all four items of apparent density, tensile strength, heat resistance and electrical conductivity of the additively manufactured object (copper alloy part) are "○". B: Of the apparent density, tensile strength, heat resistance, and electrical conductivity of an additively manufactured object (copper alloy part), three are rated "○" and one is rated "△." C: The apparent density of the additively manufactured object (copper alloy part) is such that two of the following characteristics are rated as "○" and two as "△" among the tensile strength, heat resistance, and electrical conductivity. D: The apparent density of the additively manufactured object (copper alloy part) is such that one of the following characteristics is "○": tensile strength, heat resistance, and electrical conductivity, and the other three are "△". E: At least one of the apparent density, tensile strength, heat resistance, and electrical conductivity of the additive manufactured product (copper alloy part) is marked "X," or the additive manufactured product could not be formed.

[0046] [Table 1]

[0047] From the results shown in Table 1, Examples 1 to 11 In all of the comparative examples, the contents of Cr and Zr were within the range of the present invention, the apparent density of the additively molded product (copper alloy part) was 94% or more, the tensile strength was 200 MPa or more, and at least one of the electrical conductivity and heat resistance was "△" or more, and the overall judgment was a pass level of "A" to "D". On the other hand, in the comparative examples 1 to 3, since none of them contained Zr, the apparent density of the additively molded product (copper alloy part) was less than 94%, the heat resistance was "△", the electrical conductivity was "×" or "△", and the overall judgment was "E" and unsuccessful. In the comparative example 4, the Cr and Zr contents were higher than the appropriate range of the present invention, so it was not possible to form an additively molded product (copper alloy part). In the comparative example 5, since neither Cr nor Zr was contained, the apparent density of the additively molded product (copper alloy part) was less than 94%, the tensile strength was less than 200 MPa, "×", and the heat resistance was also "×", and the overall judgment was "E". [Industrial Applicability]

[0048] According to the present invention, it is possible to provide a copper alloy powder that enables the production of an additively shaped product having all of high strength, high electrical conductivity, and excellent heat resistance, an additively shaped product, a method for producing an additively shaped product, and various metal parts such as motor brushes, brake pads, electrodes for resistance welding, electrodes for electrical discharge machining, slip rings, and bearings. The additively shaped product produced from the copper alloy powder of the present invention can be applied to various metal parts, and is particularly suitable for use in motor brushes, brake pads, electrodes for resistance welding, electrodes for electrical discharge machining, slip rings, bearings, and the like. [Explanation of symbols]

[0049] 10 Resistance welding electrodes 20 Electrode for electrical discharge machining

Claims

1. A laser beam having a wavelength of 1.2 μm or less, the laser beam containing Cr and Zr in order to increase the light absorption rate of a fiber laser having a wavelength of 1.065 μm, A Cu-Cr-Zr alloy containing, by mass%, 0.20 to 1.00% Cr, 0.50 to 0.80% Zr, and the balance being copper and unavoidable impurities; The average particle size is in the range of 10 μm or more and 40 μm or less, A copper alloy powder for additive manufacturing, characterized in that the 50% particle diameter (d50) is 29 to 39 μm and the 10% particle diameter (d10) is 13 to 25 μm in an integrated particle size distribution measured on a volume basis.

2. An additive manufacturing product formed by melting and solidifying a copper alloy powder, the copper alloy powder containing Cr and Zr to increase the light absorption rate of a fiber laser having a wavelength of 1.065 μm and, by mass%, Cr: 0.20-1.00%, Zr: 0.50-0.80%, with the remainder being copper and unavoidable impurities, the copper alloy powder having an average particle size in the range of 10 μm to 40 μm and an integrated particle size distribution measured on a volume basis having a 50% particle size (d50) of 29-39 μm and a 10% particle size (d10) of 13-25 μm, The layered object has an apparent density of 94% or more and 100% or less, and an electrical conductivity of 50% IACS or more.

3. The layered product according to claim 2 , wherein the size of the precipitates present in the layered product is 5 μm or less.

4. A motor brush formed using the copper alloy powder according to claim 1 or the layered object according to claim 2 or 3.

5. A brake pad formed using the copper alloy powder according to claim 1 or the layered product according to claim 2 or 3.

6. A slip ring formed using the copper alloy powder according to claim 1 or the layered product according to claim 2 or 3.

7. A bearing formed using the copper alloy powder according to claim 1 or the layered product according to claim 2 or 3.

Citation Information

Patent Citations

  • First wall component of nuclear fusion reactor

    JP2007171198A

  • Copper alloy material

    JP2017088949A

  • Metal powder, method for producing laminated molding and laminated molding

    JP2017115220A

  • Manufacturing method of laminate molded article and laminate molded article

    JP2018070914A

  • Copper alloy powder, heat treatment method for multilayer shaped structure, method for producing copper alloy shaped structure, and copper alloy shaped structure

    JP2019070169A